2000
DOI: 10.1080/10584580008222263
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature processing of lanthanum doped PZT thin films

Abstract: PLZT .5/30/70 sols for thin film deposition have been prepared from lead oxide, lanthanum nitrate and transition metal n-butoxides in a series of etheralcohols. After the low temperature heat treatment at 200°C for 2 minutes and at 400°C for 5 minutes the PLZT 5/30/70 thin films crystallize in the perovskite phase and exhibit ferroelectric response. To our knowledge, this is the lowest crystallization temperature of perovskite phase observed for titanium rich PLZT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Their results show that the (1 0 0) plane has the lowest surface energy, since the (1 0 0) plane has the highest planar atomic density and is electrically neutral. Some (1 0 0) oriented Pb-based ferroelectric thin films, such as (Pb,La)TiO 3 [9] and (Pb,La,Ca)TiO 3 [4,10], have been reported recently. For porous thin films, nucleation can occur at the surface of pores besides both the aforementioned factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results show that the (1 0 0) plane has the lowest surface energy, since the (1 0 0) plane has the highest planar atomic density and is electrically neutral. Some (1 0 0) oriented Pb-based ferroelectric thin films, such as (Pb,La)TiO 3 [9] and (Pb,La,Ca)TiO 3 [4,10], have been reported recently. For porous thin films, nucleation can occur at the surface of pores besides both the aforementioned factors.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroelectric thin films have been deposited by a variety of techniques, such as pulsed laser deposition [1], chemical vapor deposition [2], RF magnetron sputtering [3], and chemical solution deposition (CSD) [4]. Of various techniques for preparing ferroelectric thin films, the CSD method holds attractive advantages due to the fact that extremely uniform compositions over large areas can be obtained through a simple process and at low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…also prepared ferroelectric Ti-rich PZT films at 400C with considerable P R values ( 30 µC cm -2 ) from high homogeneous solutions. [66,69,96,97] These were synthesized by a selective modification of the Zr reagent with acetic acid that led to precursors formed by dimeric Zr organizations with bridgindg alkoxide groups.…”
Section: Iii1 Molecular Design Of Metal Precursors In Solutionmentioning
confidence: 99%
“…1). [11,12,14,39,40,44,46, Fukushima et al, [74] and Budd et al, [75,76] were among the first that demonstrated the successful fabrication of ferroelectric oxide thin films (PbTiO 3 , Pb(Zr,Ti)O 3 , PZT and 2014 [39] 2010 [46] 2019 [40] 2017 [44] 2017 [73] 2015 [72] 2014 [11] 2020 [71] 2011 [63][64][65] 2014 [62] 2008 [68] 2010 [67] 1999 [61] 2020 [70] 2003 [69] 2004 [12] 2000 [66] 2014 [62] 2016 [58] 2008 [57] 2017 [56] 2008 [14] 2001 [60] 2013 [59] 2018 [52] 2003 [53] 2000 [54] 2009 [55] The graphic shows the ferroelectric composition of the film, the processing temperature at which they were processed and the ferroelectric remanent polarization (PR) measured in them. The CSD strategy/ies used for the low-temperature solution processing of the films are also shown.…”
Section: Introductionmentioning
confidence: 99%